2017
DOI: 10.1038/eye.2017.73
|View full text |Cite|
|
Sign up to set email alerts
|

Osmoprotectants, carboxymethylcellulose and hyaluronic acid multi-ingredient eye drop: a randomised controlled trial in moderate to severe dry eye

Abstract: PurposeTo assess the safety and efficacy of an eye drop combining osmoprotectants, carboxymethylcellulose and hyaluronic acid (O/CMC/HA) in reducing symptomatic, moderate to severe dry eye, compared with HA.MethodsIn this investigator-masked, randomised study, patients instilled 1–2 drops/eye of O/CMC/HA or HA (2–6 times/day) for 3 months. Primary endpoint: mean change in Global Ocular Staining Score (GOSS) from baseline at day 35. Noninferiority of O/CMC/HA was tested in the per-protocol population; if achiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 23 publications
0
24
0
Order By: Relevance
“…The effectiveness of the CMC–HA combination at 0.5%/0.1% concentrations (Optive Fusion; Allergan plc, Dublin, Ireland) has been reported recently in two multicenter, randomized clinical trials involving patients with mild to severe dry eye. 39 , 40 The effects of this combination on dry eye symptoms that develop after cataract surgery have also been investigated in a randomized study. 41 Moreover, preservative-free and multidose preserved formulations with this combination of polymers have now become available.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of the CMC–HA combination at 0.5%/0.1% concentrations (Optive Fusion; Allergan plc, Dublin, Ireland) has been reported recently in two multicenter, randomized clinical trials involving patients with mild to severe dry eye. 39 , 40 The effects of this combination on dry eye symptoms that develop after cataract surgery have also been investigated in a randomized study. 41 Moreover, preservative-free and multidose preserved formulations with this combination of polymers have now become available.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in a randomized, investigator-blinded prospective study, the efficacy and safety of the combination of osmoprotectants/CMC/HA were evaluated in terms of the reduction of symptoms in patients with moderate-to-severe DED, in comparison with a compound with 0.18% HA. 70 The results of this study showed that, with regard to the improvement of DED symptoms, the combined formulation of HA/CMC/osmoprotectants was not inferior to 0.18% HA. Also, compared with 0.18% HA, a higher percentage of patients reported a significantly lower amount of severe itching/burning, foreign body sensation (grittiness), and ocular pain/irritation after 3 months of treatment with the combination of osmoprotectants/CMC/HA.…”
Section: Introductionmentioning
confidence: 62%
“…Also, compared with 0.18% HA, a higher percentage of patients reported a significantly lower amount of severe itching/burning, foreign body sensation (grittiness), and ocular pain/irritation after 3 months of treatment with the combination of osmoprotectants/CMC/HA. 70 Furthermore, a lower number of patients presented ocular pain/irritation on day 35 of treatment in the group treated with the combination of osmoprotectants/CMC/HA in comparison with HA. 70 …”
Section: Introductionmentioning
confidence: 91%
“…Artificial tears, generally based on water-retentive polymers such as carboxymethylcellulose and hyaluronic acid, replace and/or reproduce the natural tear film and control the inflammatory response [ 31 , 32 , 33 ]. An improvement of the efficacy of tear substitutes can be obtained with the addition of osmoprotective agents that contribute to the stabilization of the cell volume under hyperosmotic stress, limiting cellular apoptotic phenomena and inflammation processes [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…A positive effect on cell viability in the presence of taurine supplementation was observed by Shioda et al [ 12 ] that was ascribed to a possible antioxidant activity or membrane stabilization effect of taurine, a well-known osmolyte substance [ 13 ]. Osmoprotective substances such as erythritol, l -carnitine, and glycerine in combination with carboxymethylcellulose were more efficient in controlling primary outcomes (e.g., tear osmolarity, Schirmer-I test scores) and were consequently able to reduce the cellular stress level at the ocular surface in humans [ 14 ]. In addition, the ability of trehalose to allow for the survival of cells in unfavourable conditions, such as those present in a hyperosmotic environment, was exploited for use in the development of eye drops.…”
Section: Introductionmentioning
confidence: 99%